2022
DOI: 10.1111/imm.13526
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines, adjuvants and key factors for mucosal immune response

Abstract: Vaccines are the most effective tool to control infectious diseases, which provoke significant morbidity and mortality rates. Most vaccines are administered through the parenteral route and can elicit a robust systemic humoral response, but they induce a weak T-cell-mediated immunity and are poor inducers of mucosal protection. Considering that most pathogens enter the body through mucosal surfaces, a vaccine that elicits protection in the first site of contact between the host and the pathogen is promising. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 151 publications
1
39
0
Order By: Relevance
“…Respiratory mucosal immunity plays an important front‐line role against respiratory viral infections. Especially, S‐IgA in the respiratory mucosa protects against invasion of viruses into mucosal cells, resulting in prevention of infection and transmission of pathogens to other individuals 12,25 . Our results demonstrated that S1‐SF‐10‐TA vaccine induced S1‐specific IgG and IgA ASCs in the spleen and lungs (Figure 3) and S1‐specific antibodies in the serum and BALF (Figures 1 and 2A–D), which efficiently inhibited S1/ACE2 binding (Figure 2E–H).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Respiratory mucosal immunity plays an important front‐line role against respiratory viral infections. Especially, S‐IgA in the respiratory mucosa protects against invasion of viruses into mucosal cells, resulting in prevention of infection and transmission of pathogens to other individuals 12,25 . Our results demonstrated that S1‐SF‐10‐TA vaccine induced S1‐specific IgG and IgA ASCs in the spleen and lungs (Figure 3) and S1‐specific antibodies in the serum and BALF (Figures 1 and 2A–D), which efficiently inhibited S1/ACE2 binding (Figure 2E–H).…”
Section: Discussionmentioning
confidence: 68%
“…Since the mucosa is equipped with exclusion systems, namely, the cilia, mucus, and various proteases, against foreign substances including vaccine antigens, 11 the use of vaccines that contain antigen alone is unlikely to produce protective immunity. Thus, for successful mucosal vaccination, live virus vaccines and mucosal adjuvants that enhance the vaccine effects have been developed worldwide 12 . However, the live attenuated vaccines, such as Flumist®, have problems related to their efficacy and safety, and thus, their worldwide use is limited 13 …”
Section: Introductionmentioning
confidence: 99%
“…Especially, S-IgA in the respiratory mucosa protects against invasion of viruses into mucosal cells, resulting in prevention of infection and transmission of pathogens to other individuals. 12,25 Our results demonstrated that S1-SF-10-IT vaccine induced S1-specific IgG and IgA ASCs in the spleen and lungs (Figure 3) and S1specific antibodies in the serum and BALF (Figure 1, 2A-D), which efficiently inhibited S1/ACE2 binding (Figure 2E-H). The S1-AS03-IM induced S1-specific IgG in the serum and BALF (Figure 2A, B), but not S1-specific IgA in serum and BALF (Figure 2C, D), and S1-specific IgA ASCs in the spleen and lungs (Figure 3B, D).…”
Section: Discussionmentioning
confidence: 77%
“…Thus, for successful mucosal vaccination, live virus vaccines and mucosal adjuvants that enhance the vaccine effects, have been developed worldwide. 12 However, the live attenuated vaccines, such as Flumist ® , have problems related to their efficacy and safety and thus their worldwide use is limited. 13 To overcome these problems, we reported previously the use of an antigen delivery type adjuvant, 14 pulmonary surfactant (PS)-based compound, surfacten ® , as an effective and safe intranasal mucosal adjuvant for influenza ether-split hemagglutinin vaccine (HAv) and that it enhanced the production of both HAv-specific IgG in serum and S-IgA in the respiratory mucosae of mice and swine.…”
mentioning
confidence: 99%
“…Although mucosal vaccines are powerful tools for induction of mucosal immunity [ 1 ], there are still only a few on the market, owing to several technological and biological hurdles impeding the development of efficient formulations [ 2 ]. Among mucosal administration sites, sublingual (SL) mucosa presents an accessible and thin epithelium that has exhibited considerable potential to induce efficient vaccine response in non-human primates [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%